ESTUDO COMPARATIVO DA COMPOSIÇÃO QUÍMICA DOS ÓLEOS ESSENCIAIS DAS FOLHAS DAS ESPÉCIES: S. LENTISCIFOLIUS, S. TEREBINTHIFOLIUS, S. MOLLE E S. POLYGAMUS COLETADAS EM IJUÍ - Gehrke, Ilaine T. S.; Morel, Ademir F.; Tormöhlen, Adriane; Corrêa, Jéssyca B. (Salão do Conhecimento, 2013)
Resumo